2012
DOI: 10.1093/nar/gkr1220
|View full text |Cite
|
Sign up to set email alerts
|

End-to-end attraction of duplex DNA

Abstract: Recent experiments [Nakata, M. et al., End-to-end stacking and liquid crystal condensation of 6 to 20 basepair DNA duplexes. Science 2007; 318:1276–1279] have demonstrated spontaneous end-to-end association of short duplex DNA fragments into long rod-like structures. By means of extensive all-atom molecular dynamic simulations, we characterized end-to-end interactions of duplex DNA, quantitatively describing the forces, free energy and kinetics of the end-to-end association process. We found short DNA duplexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
105
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(121 citation statements)
references
References 59 publications
11
105
1
Order By: Relevance
“…In a simulation of two axially aligned DNA fragments kept a small distance apart, we observe a very swift approach and stacking in the FH configuration at a distance of 3.75Å validating the above observations ( Figure S3A-B) [33]. Our binding energy values are consistent with the value (6.3 kcal/mol) obtained by Aksimentiev et al [44] for the end-to-end stacking of 10-bp long dsDNA which were free to rotate about their common axis contrary to ours. Being free to rotate, the azimuthal sampling of their DNA fragments and hence the accessibility of the interfacial bases to water due to thermal uctuations is in-between the two congurations that we have used, resulting in an intermediate value of binding energy.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In a simulation of two axially aligned DNA fragments kept a small distance apart, we observe a very swift approach and stacking in the FH configuration at a distance of 3.75Å validating the above observations ( Figure S3A-B) [33]. Our binding energy values are consistent with the value (6.3 kcal/mol) obtained by Aksimentiev et al [44] for the end-to-end stacking of 10-bp long dsDNA which were free to rotate about their common axis contrary to ours. Being free to rotate, the azimuthal sampling of their DNA fragments and hence the accessibility of the interfacial bases to water due to thermal uctuations is in-between the two congurations that we have used, resulting in an intermediate value of binding energy.…”
Section: Resultssupporting
confidence: 91%
“…al. [44] in their study using atomistic simulation, also found two preferential values for the azimuthal angle. De Michele et al [57] find the peak for end-to-end distance distribution at around 3.7 A, while, Maffeo et al [44] report peak at around 5Å.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Classical all-atom approaches, where every atom of DNA and the surrounding solvent is modelled as a point particle with effective interactions, have been widely employed to study small DNA motifs 14,15 and have recently been applied to larger DNA systems. [16][17][18] However, simulating rare-event processes such as the breaking or formation of base pairs remains a challenge with these models, with µs time scales being the limit of what is currently accessible. 18 At the other end of the scale, theoretical approaches have been developed to understand certain large-scale properties of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of EtBr might also be related to the absence in GCTA of the terminal phosphate, which is instead present in the other two molecules. Atomistic computer simulations have suggested that DNA stacking interactions in presence of phosphate terminal is stronger and more constraining to the natural helical continuity [21]. Thus, it could be argued that the presence of EtBr in GCTA has a more relevant role in stabilizing the interaction across the adjacent coaxially stacked strands, which is in this case weaker because of the absence of phosphate termination.…”
Section: Phase Behavior Of Gctamentioning
confidence: 99%